2017
DOI: 10.1017/aee.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Undergraduate Management Curricula: Changes Over a 5-Year Period

Abstract: Global initiatives and a rapidly expanding academic literature identify the responsibility that universities have to incorporate sustainability education into their curricula. This study had two aims: first, to investigate the extent to which Australian undergraduate management curricula explicitly identified a focus on sustainability and, second, to examine the changes that had occurred between 2009 and 2014. A web-based content analysis was undertaken to gain a snapshot view of the emphasis placed on sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Nevertheless, despite two decades of calls for changes to business and management education to include sustainability education (Cortese, 2003;Galea, 2004;Springett, 2005;Thomas, 2004), these calls have only partially been heeded (Dameron & Durand, 2017;Fisher & Bonn, 2017;Setó-Pamies & Papaoikonomou, 2016), often with standalone courses in various curricula (Brueckner et al, 2017;Doh & Tashman, 2014) or weak sustainability orientation (Landrum & Ohsowski, 2017). As a result, business school curricula are failing to develop responsible leaders and to influence managerial and professional attitudes and practices that drive positive social change (Dameron & Durand, 2017;Fagan, 2009;Green et al, 2017;Rezaee et al, 2016) as well as the critical thinking and decision-making skills required for modern management (Kaltenecker & Kahle-Piasecki, 2018;Sidiropoulos, 2014).…”
Section: Discourse Analytical Skills To Teach Sustainability In Busin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, despite two decades of calls for changes to business and management education to include sustainability education (Cortese, 2003;Galea, 2004;Springett, 2005;Thomas, 2004), these calls have only partially been heeded (Dameron & Durand, 2017;Fisher & Bonn, 2017;Setó-Pamies & Papaoikonomou, 2016), often with standalone courses in various curricula (Brueckner et al, 2017;Doh & Tashman, 2014) or weak sustainability orientation (Landrum & Ohsowski, 2017). As a result, business school curricula are failing to develop responsible leaders and to influence managerial and professional attitudes and practices that drive positive social change (Dameron & Durand, 2017;Fagan, 2009;Green et al, 2017;Rezaee et al, 2016) as well as the critical thinking and decision-making skills required for modern management (Kaltenecker & Kahle-Piasecki, 2018;Sidiropoulos, 2014).…”
Section: Discourse Analytical Skills To Teach Sustainability In Busin...mentioning
confidence: 99%
“…In fact, Scherer and Voegtlin (2020) found that for corporations to enjoy long-term success, involving stakeholders, not shareholders, facilitates inclusion, increases trust, and cultivates cocreation and knowledge contribution through a broader range of perspectives of sociocultural and environmental conditions. Therefore, to meet sustainability and social consciousness imperatives, business schools must implement transformative curricula aimed at educating responsible, credible business leaders of the future (Fisher & Bonn, 2017).…”
mentioning
confidence: 99%
“…Traditionally, management education did not focus on the sustainable development of either business or society (Fisher and Bonn 2017). Various scholars agree that it focused mainly on teaching business students and executives about various ways of operating business with the end goal of maximising profit, albeit at minimal financial loss (Bristow 2011 Moon (2014) -that there is a lack of socio-economic focus in management education programmes, thereby creating a ripple effect on how business executives make decisions.…”
Section: Overview Of Management Educationmentioning
confidence: 99%
“…The concept of sustainable economic development was introduced in 1987, but the "sustainable shift" is slow to reach academic marketing education. Even though sustainability related skills are viewed as increasingly important for managers (Fisher, Bonn 2017), academic business programs are reluctant to adopt sustainability related content and only a small portion of marketing courses is devoted to sustainability education (Barber et al 2014;Fisher, Bonn 2017;Friel, McLaughlin 2013;Perera, Hewege 2016). Especially business schools tend to base their programs on a businesscentred worldview in which the success of society depends on the success of companies (Beddewela et al 2017) and in which the success of companies equals profit.…”
Section: Introductionmentioning
confidence: 99%